Les Paradoxes de la Traduction - Ouni, Abdessattar; Khaskhossi, Ahmed (المركز الوطني للترجمة, 2015)
Although translating a text from its source language to other target languages has an old practice dating back to the first invention of writing, studying issues related to the theorical aspect of translation has been relatively a new academic issue. It has been led to raise several questions, the present article is limited to answerinsg the following questions: Why haven't researchers in translation reached a compromise on an agreed upon definition of translation ? Why haven’t defined the field of research in Translation ? Are the measures adopted by those who categorized translation accurate and characterized by a clear distinctive approach ? To what extent have the ideas related to translation contributed to elaborating the cultural, linguistic, structural and stylistic obstacles that have been increasing from the Hellenic Age to now. Why have these obstacles preventend translation from reaching the stage of complete faithfulness to the content of the source text and its artistic features ? When will research in translation become an independent science with independent content, methodology and terminology ?
لئن كان نقل النّص المكتوب من لسانه الأصلي إلى بعض الألسنة الأخرى ممارسة عريقة ترقى نشأتها إلى زمان اختراع الكتابة فإنّ درس القضايا النّظريّة للترجمة حديث العهد نسبيّا، وقد أسفر عن طرح أسئلة عديدة ينحصر مدار هذا المقال في الإجابة ع يلي منها: لماذا لم يتوصّل الباحثون في الترجمة إلى الاتفاق على تعريف موحّد لها وإلى تحديد موضوع البحث فيها؟ هل تتح المقاييس التي اعتمدها مصنّفو الترجمة إلى أنواع بالدّقّة وبكفاية تمييزيّة ثابتة؟ إلى أيّ مدى أسهمت الأفكار المتعلّقة بالترجمة والّتي ما فتئت تتكاثر بمختلف الحضارات منذ العصر الهلّيني إلى الآن في بلورة العوائق الثّقافيّة واللّغويّة والتّركيبيّة والأسلوبيّة الحائلة دون بلوغ الترجمة درجة الوفاء التّامّ لمضمون النّص الأصليّ ولخصائصه الفنيّة ؟ متى يصبح البحث في الترجمة علما مستقلاّ بموضوعه ومناهجه ومصطلحاته عن سائر العلوم؟
Keywords: علم الترجمة -- النظريات الأدبية -- التراكيب اللغوية -- القضايا النظرية -- مستخلصات الأبحاث